Polymer mortar with carbon dioxide lasting absorption function and preparation method thereof
By adding organic amines with special structures to the cement-based material, polymer mortar with a lasting absorption function of carbon dioxide was developed, which solved the problems of limited CO2 capture amount and short duration in the prior art, achieved continuous CO2 capture and mechanical properties of polymer mortar, and reduced carbon emissions of cement products.
Patent Information
- Application Number
- CN202411868219.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The CO2 capture technology in existing cement-based materials has problems such as limited capture volume, short sustainability and cumbersome construction, and it is difficult to effectively reduce carbon emissions in the cement industry.
A polymer mortar with a lasting absorption function of carbon dioxide is developed. By adding organic amines with special structures to the material, a covalent bond is used to form a silicon oxygen bond with the polymer mortar, the amount of CO2 fixed is increased, and CO2 is captured and fixed under high humidity environment.
The continuous CO2 capture function of polymer mortar in high humidity environment is realized, and the fixed CO2 is converted into water-insoluble CaCO3, filling cement pores, enhancing mechanical properties, and reducing the carbon emissions of cement products throughout the life cycle.
Smart Images

Figure BDA0005195047820000031 
Figure BDA0005195047820000032 
Figure BDA0005195047820000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of green building materials, and particularly relates to a polymer mortar with a carbon dioxide durable absorption function and a preparation method thereof. Background Art
[0002] As the world's population continues to grow, people's demand for improved quality of life has led to an increase in global CO2 emissions and a sharp increase in greenhouse gases, posing a threat to people's life systems. Against this background, countries around the world have jointly reduced CO2 emissions through a global agreement.
[0003] The building materials industry is an important high-energy consumption and high-emission industry in my country. It is also a key industry for my country to control and reduce greenhouse gas emissions. It is imperative to continuously develop green and low-carbon products. The cement industry is one of the key industries for CO2 emissions, and its direct carbon emissions account for about 1 / 4 of the total global industrial carbon emissions. my country is the country that produces the most cement in the world. In 2020, my country's cement production was 24×10 8 t, accounting for more than half of the world's total cement production. Studies have shown that direct CO2 emissions from my country's cement industry account for about 12% of the country's total CO2 emissions, of which industrial process emissions account for more than 60% of the country's industrial process emissions. In all aspects of cement manufacturing, although a variety of emission reduction measures have been taken, the two steps of fossil fuel combustion and carbonate ore decomposition are still the main sources of carbon emissions. According to the life cycle assessment theory, cement carbon emissions exist not only in the production stage, but also in the transportation, use, service and waste recycling links. Therefore, the inevitable carbon emissions in the production process should be balanced by active carbon capture or solidification measures in the transportation, application, maintenance and recycling stages of cement. Given the importance of the cement industry in addressing challenges such as climate change, environmental risks and energy resource constraints, conducting research on CO2 capture and fixation technology based on cement is essential to promote the green transformation and high-quality development of the industry.
[0004] Carbon fixation in cement-based materials refers to the capture and fixation of CO2 during the maintenance or use stage of cement-based materials. As a mineral storage technology for CO2, carbon fixation in cement-based materials can capture and fix CO2 during the use stage of cement, offset the CO2 emitted during the production stage, and thus reduce the carbon emissions of cement products throughout their life cycle. It is a new idea for cement-based material research. However, there are currently few studies on this field at home and abroad, and most of them focus on the compression, capture and separation of carbon dioxide in the atmosphere. Even if CO2 capture technology is applied in building materials, most of them are through post-impregnation and re-coating methods. This method not only has a limited amount of CO2 capture, but also has a short duration, cumbersome construction, and has no practical application value.
[0005] Therefore, in view of the huge amount of cement used in my country every year, it is necessary for us to develop cement-based carbon-fixing materials, that is, a polymer mortar with the function of long-term absorption of carbon dioxide. Before the material is used, it has the function of capturing carbon dioxide, reducing secondary construction, and complying with relevant policies on low-carbon emission reduction. Summary of the invention
[0006] In view of the problems and shortcomings in the prior art, the present invention aims to provide a polymer mortar with a long-lasting carbon dioxide absorption function and a preparation method thereof.
[0007] In order to achieve the purpose of the present invention, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a polymer mortar with a carbon dioxide durable absorption function. The polymer mortar is mainly made of the following raw materials in parts by weight: 500-800 parts of cement, 400-800 parts of 10-20 mesh quartz sand, 400-800 parts of 20-40 mesh quartz sand, 400-800 parts of 40-70 mesh quartz sand, 200-500 parts of 70-100 mesh quartz sand, 20-50 parts of silica fume, 10-30 parts of redispersible latex powder, 1-5 parts of an admixture, and in addition, 1%-15% of the total weight of the above raw materials is added with an organic amine;
[0009] The organic amine is a double-terminal primary amine containing a silicon-oxygen bond, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is used as a capping agent to obtain an amino-terminated hydrogen-containing polysiloxane intermediate through a ring-opening reaction of 1,3,5,7-tetramethylcyclotetrasiloxane; the intermediate is subjected to a hydrosilylation reaction with γ-methacryloxypropyltrimethoxysilane to obtain the intermediate;
[0010] The additive is one or more of a water reducing agent, a defoaming agent, and a swelling agent.
[0011] Preferably, the molar ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to 1,3,5,7-tetramethylcyclotetrasiloxane is (4-6):1.
[0012] Preferably, the molar ratio of γ-methacryloxypropyltrimethoxysilane to the amino-terminated hydrogen-containing polysiloxane intermediate is (0.9-1.1):1.
[0013] Preferably, the cement is one or more of fly ash cement 425, fly ash cement 525, slag silicate cement 425, slag silicate cement 525, general silicate 425 cement, and general silicate 525 cement.
[0014] Preferably, the redispersible latex powder is one or more of ethylene / vinyl acetate copolymer, vinyl acetate / versatate copolymer / acrylic acid copolymer.
[0015] The polymer mortar with the function of long-term carbon dioxide absorption of the present invention has the following carbon fixation mechanism:
[0016] Primary and secondary amines easily react with CO2 to form relatively stable carbamates:
[0017] RNH2 + CO2 → RNH2 + COO - (1)
[0018] In high humidity environments, carbamates partially hydrolyze:
[0019] RNH2+COO - + H2O→HCO3 - +CO3 2- (2)
[0020] In a strongly alkaline environment, HCO3 - It is difficult to exist, and CO3 is generated 2- .
[0021] CO3 2- + Ca 2+ →CaCO3 (3)
[0022] The present invention also provides a method for preparing the above-mentioned polymer mortar with the function of durable carbon dioxide absorption, which is specifically: cement, 10-20 mesh quartz sand, 20-40 mesh quartz sand, 40-70 mesh quartz sand, 70-100 mesh quartz sand, silica fume, redispersible latex powder, organic amine and admixture are mixed according to mass parts, stirred evenly to obtain dry mortar, 10% to 15% of water by mass of the dry mortar is added and mixed evenly to obtain polymer mortar.
[0023] Preferably, the pH value of the polymer mortar is 12-15.
[0024] Preferably, the polymer mortar system c(OH - ) value is 0.01mol / L~10mol / L.
[0025] The organic amine is prepared by the following method:
[0026] S1: Add end-capping agents 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 1,3,5,7-tetramethylcyclotetrasiloxane (D4H) into a reactor equipped with a condensation reflux device, introduce protective gas, raise the temperature to 70-90° C., add an alkaline catalyst, and react for 7-10 hours to obtain an amino-terminated hydrogen-containing polysiloxane intermediate, the structure of which is shown in Formula 1;
[0027]
[0028] S2: Under a protective gas atmosphere, toluene and γ-methacryloxypropyltrimethoxysilane (KH570) are added to the reactor, the temperature is raised to 60-80°C, Karstedt catalyst is added, and then an amino-terminated hydrogenated polysiloxane intermediate is added, the reaction is carried out for 0.5-3h, and toluene is removed to obtain an organic amine, the structure of which is shown in Formula 2.
[0029]
[0030] Preferably, the alkaline catalyst is one or more of sodium hydroxide, potassium hydroxide, and tetramethylammonium hydroxide.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] (1) The polymer mortar of the present invention is added with an organic amine having a special structure, which is a double-terminal primary amine containing a silicon-oxygen bond. The double-terminal amino organic amine has a large molecular volume, which can increase the amount of CO2 fixed and continuously absorb a large amount of CO2 in the air. The silicon-oxygen bond of the organic amine can form a stronger covalent bond with the polymer mortar, which has an excellent anchoring effect, avoids the loss of the organic amine in the later stage, and can continuously capture CO2. The polymer mortar in the later stage still has an excellent CO2 capture function in a high humidity environment.
[0033] (2) Under high humidity conditions, the organic amine in the polymer mortar of the present invention will capture CO2 that will penetrate into the pores of the mortar, react with the hydration product Ca(OH)2 inside the cement mortar, and then be converted into a large amount of CaCO3, so that the organic amine polymer mortar can fix CO2. At the same time, the solidified product CaCO3 is insoluble in water, which plays a role in filling the pores of the cement and enhancing the mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 TG and DTG curves of blank control 2 polymer mortar;
[0035] Figure 2 TG and DTG curves of polymer mortar of Example 5. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0037] Example 1 Preparation of a double-terminal primary amine containing a silicon-oxygen bond
[0038] A preparation method of a double-terminal primary amine containing a silicon-oxygen bond comprises the following steps:
[0039] S1: Preparation of amino-terminated hydrogenated polysiloxane intermediates by D4H ring-opening reaction
[0040] The end-capping agent 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 1,3,5,7-tetramethylcyclotetrasiloxane (D4H) were added in a molar ratio of 4.5:1 into a reaction vessel equipped with a condensation reflux device, and nitrogen was introduced throughout the process for protection. The temperature was raised to 75° C., and the catalyst potassium hydroxide was added. The reaction was carried out for 10 hours to obtain an amino-terminated hydrogen-containing polysiloxane intermediate, whose structure is shown in Formula 1.
[0041] S2: Preparation of target product by hydrosilylation reaction
[0042] Under an inert gas protection atmosphere, toluene and γ-methacryloxypropyltrimethoxysilane (KH570) were added to the reactor, the temperature was raised to 70°C, Karstedt catalyst was added, and then the amino-terminated hydrogen-containing polysiloxane intermediate was added to the reaction vessel. The molar ratio of KH570 to the intermediate was 1:1. The reaction was kept warm for 1 hour. After the reaction was completed, the solvent toluene was removed to obtain a double-terminal primary amine containing a silicon-oxygen bond, whose structure is shown in Formula 2.
[0043] Example 2
[0044] A polymer mortar with a function of persistently absorbing carbon dioxide, mainly made of the following raw materials in parts by weight:
[0045] 650 parts of cement;
[0046] 500 parts of 10-20 mesh quartz sand;
[0047] 400 parts of 20-40 mesh quartz sand;
[0048] 450 parts of 40-70 mesh quartz sand;
[0049] 200 parts of 70-100 mesh quartz sand;
[0050] Silica fume 25 parts;
[0051] 15 parts of redispersible latex powder;
[0052] 4 parts of admixture;
[0053] In addition, 1% of the total weight of the above raw materials is added into an organic amine.
[0054] The cement is ordinary silicon 425 cement, the redispersible latex powder is ethylene / vinyl acetate copolymer, the admixture is a water reducing agent, and the organic amine is a double-terminal primary amine containing a silicon-oxygen bond prepared in Example 1.
[0055] Preparation method of polymer mortar: stir the above raw materials evenly to obtain dry mortar, add 13% water of the dry mortar mass and mix evenly to obtain polymer mortar with carbon dioxide long-lasting absorption function, take part of the slurry to measure the pH value. Pour the remaining mortar into a standard mold, cure under standard humidity and temperature conditions until final setting, remove the mold and place it in a carbonization box with a CO2 concentration of 20%, and cure it under standard humidity and temperature conditions for 28 days, during which relevant performance tests are carried out.
[0056] Example 3
[0057] Example 3 is substantially the same as Example 2, except that the amount of organic amine added is 3%.
[0058] Example 4
[0059] Example 4 is substantially the same as Example 2, except that the amount of organic amine added is 5%.
[0060] Example 5
[0061] Example 5 is substantially the same as Example 2, except that the amount of organic amine added is 7%.
[0062] Example 6
[0063] Example 6 is substantially the same as Example 2, except that the amount of organic amine added is 9%.
[0064] Example 7
[0065] Example 7 is substantially the same as Example 2, except that the amount of organic amine added is 11%.
[0066] Example 8
[0067] Example 8 is substantially the same as Example 2, except that the amount of organic amine added is 12%.
[0068] Example 9
[0069] Example 9 is substantially the same as Example 2, except that the amount of organic amine added is 15%.
[0070] Blank control 1
[0071] The raw material composition of blank control 1 is substantially the same as that of Example 2, except that the amount of organic amine added is 0.
[0072] Preparation method of polymer mortar: stir the above raw materials evenly to obtain dry mortar, add 13% water of the dry mortar mass and mix evenly to obtain polymer mortar, take part of the slurry to measure the pH value. Pour the remaining mortar into a standard mold and cure it under standard humidity and temperature conditions for 28 days as a blank control group 1.
[0073] Blank control 2
[0074] The raw material composition of blank control 2 is substantially the same as that of Example 2, except that the amount of organic amine added is 0. The preparation method of polymer mortar is the same as that of Example 2.
[0075] (I) Mechanical properties test
[0076] The mechanical properties of the polymer mortars prepared in Examples 2 to 9 were tested, and the results are shown in Table 1.
[0077] Table 1 Mechanical properties test results of polymer mortars in Examples 2 to 9
[0078]
[0079] From the comparison between Examples 2 to 9 and the blank control 1, it can be seen that as the amount of organic amine added increases, the pH value of each example gradually increases, and the initial setting and final setting times become shorter and shorter. This is mainly because the higher alkali content accelerates the early hydration rate of cement and generates potassium gypsum, which becomes an important reason for the flash setting of cement. Organic amines affect the mechanical properties of polymer mortar, and the effect on the initial setting time (workability) is most obvious. When the amount of organic amine added reaches more than 10%, it is almost not workable due to the short initial setting time (21min). At the same time, the higher alkali content slightly increases the strength of cement before 7d, but reduces the later and long-term strength. Compared with the blank control 1, the blank control 2 has a larger loss in flexural and compressive strength. This is mainly because in a high concentration of CO2 environment, there is no organic amine inside the blank control 2 test block that can capture carbon dioxide, and it cannot provide an alkaline environment for the hydration system for a long time. Therefore, CO2 enters the mortar block through the gaps in the polymer mortar and reacts with Ca in the test block. 2+ The organic amine can capture CO2 and react with Ca(OH)2 in the cement hydration process to generate water-insoluble CaCO3, which can fix carbon dioxide and fill the internal pores of cement to enhance the mechanical properties.
[0080] (II) Carbon fixation test
[0081] The amount of CO2 fixation can be quantitatively characterized by thermogravimetric curves using a thermogravimetric analyzer (TGA). The method is as follows: The polymer mortar prepared in the blank control group 2 and Example 5 was subjected to thermogravimetric analysis to obtain TG and DTG curves. The TG and DTG curves of the blank control 2 are shown in FIG. Figure 1 The TG and DTG curves of Example 5 are shown in Figure 2 .
[0082] Depend on Figure 1 , Figure 2 The comparison shows that the DTG curves of the samples show two stages of rapid mass loss. In the 0-120℃ stage 1, Figure 1 In the blank group, this stage is the loss of amorphous water in the material; Figure 2 The weight loss peak in stage 1 is relatively large, and the mass loss in this stage is mainly composed of two parts: the release of CO2 captured by organic amines and the volatilization of amorphous water. In the 150-350℃ stage, according to the physicochemical properties of organic amines (the boiling point of special structure organic amines (self-made) is 227.8℃), it can be inferred that this stage is caused by the volatilization of organic amines themselves, and the mass loss of this part accounts for a small proportion. In stage 2 at 600-800℃, CaCO3 begins to decompose into CaO and CO2, and the rapid loss of mass in this stage can be seen from the DTG curve. It can be concluded from the figure that, except for the mass loss in the first stage, the amount of CO2 decomposed by CaCO3 after carbon fixation in organic amine-coated cement mortar is also greater than that in the reference mortar, indicating that more CaCO3 is generated after carbon fixation in polymer mortar than in the blank group mortar. Therefore, the quantitative value of carbon fixation in polymer mortar can be obtained by the difference between the two.
[0083] The polymer mortars prepared in Examples 2 to 9 were tested for carbon fixation using the above method, and the results are shown in Table 2. The calculation formula for the net loss of CaCO3 is as follows:
[0084]
[0085] The calculation formula for CO2 fixation is as follows:
[0086] Ca(OH)2 + CO2 = CaCO3 + H2O 44 100
[0088] M(CO2) M(CaCO3)
[0089] M(CO2)= 0.44 × M(CaCO3)
[0090] Under the atmospheric environment, we believe that the test block did not carbonize in a short period of time, that is, it did not absorb carbon dioxide, and the net loss of CaCO3 in blank group 1 was considered to be 0.
[0091] In the absence of organic amine, the amount of carbon dioxide fixed under 20% carbonization acceleration: blank group 2: 0.44×(2.77-0)=1.22, Example 5, the amount of carbon dioxide fixed by organic amine: 0.44×(57.59-2.77)=24.12.
[0092] Table 2 Carbon fixation test results of polymer mortar in Examples 2 to 9
[0093]
[0094] It can be seen from Table 2 that with the increase of organic amine content, the content of fixed CO2 also gradually increases. The blank control 2 without adding organic amine has very little fixed CO2, that is, only carbonization. Combined with the test results in Table 1, in order to obtain a polymer mortar with both workability, mechanical properties and carbon fixation, Example 5 is the most preferred embodiment of the present invention.
[0095] Comparative Example 1
[0096] The difference from Example 5 is that pentamethylenediamine is used as the organic amine.
[0097] Comparative Example 2
[0098] The difference from Example 5 is that the organic amine is hexamethylenediamine.
[0099] Comparative Example 3
[0100] The difference from Example 5 is that the organic amine is heptyl diamine.
[0101] Comparative Example 4
[0102] The difference from Example 5 is that the organic amine is octanediamine.
[0103] Comparative Example 5
[0104] The difference from Example 5 is that nonanediamine is used as the organic amine.
[0105] Comparative Example 6
[0106] The difference from Example 5 is that the organic amine is melamine.
[0107] The polymer mortars prepared with different organic amines in Comparative Examples 1 to 6 and Example 5 were tested for mechanical properties and carbon fixation, and the results are shown in Table 3. The calculation formula for the growth rate of CaCO3 fixation is as follows:
[0108]
[0109] Table 3 Performance test results of polymer mortars of comparative examples 1 to 6
[0110]
[0111] From the comparison of Comparative Examples 1 to 6 and Example 5 in Table 3, it can be seen that with the increase of aliphatic diamine chain segments, the initial setting time of polymer mortar in Comparative Examples 1 to 5 gradually increases, which is in line with the rule that the alkalinity of aliphatic diamines decreases with the increase of chain segment length after water dissolution, and the carbon fixation amount in 28 days decreases accordingly. From the change in the growth rate of CO2 fixation, it can be seen that aliphatic diamines with shorter chain segments are easily precipitated from the pores of polymer mortar in a high humidity environment, that is, the durability is poor. Comparative Example 6 uses large-volume melamine as an organic amine. Although the growth rate of CO2 fixation increases, melamine has poor solubility in water and is difficult to provide a large alkaline environment. It is greatly affected by carbonization and has a large loss of mechanical properties. Example 5 of the present invention uses a double-terminal primary amine containing a silicon-oxygen bond prepared in Example 1 for polymer mortar, which has good durability and can still fix carbon well at 28 days, and can take into account both carbon fixation performance and mechanical properties. This is because the double-terminated amino organic amine prepared in Example 1 has a larger molecular volume, which can increase the amount of CO2 fixed, and at the same time introduces a silicon-oxygen bond, which can form a Si-O-Si covalent bond with the polymer mortar, forming a more reliable anchor, avoiding the loss of the organic amine in the later stage, and can continuously capture CO2. The polymer mortar in the later stage still has excellent CO2 capture function in a high humidity environment. At the same time, the organic amine captures CO2 and reacts with Ca(OH)2 in the cement hydration process to generate water-insoluble CaCO3, which can fix carbon dioxide while filling the internal pores of the cement and enhancing the mechanical properties.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Those skilled in the art can modify or replace the technical solution of the present invention according to the idea of the present invention without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A polymer mortar with a function of long-term absorption of carbon dioxide, characterized in that: The polymer mortar is mainly made of the following raw materials in parts by weight: 500-800 parts of cement, 400-800 parts of 10-20 mesh quartz sand, 400-800 parts of 20-40 mesh quartz sand, 400-800 parts of 40-70 mesh quartz sand, 200-500 parts of 70-100 mesh quartz sand, 20-50 parts of silica fume, 10-30 parts of redispersible latex powder, 1-5 parts of admixture, and 1%-15% of the total weight of the above raw materials. Organic amine; The organic amine is a double-terminal primary amine containing a silicon-oxygen bond, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is used as a capping agent. An amino-terminated hydrogen-containing polysiloxane intermediate is prepared by a ring-opening reaction of 1,3,5,7-tetramethylcyclotetrasiloxane, and the intermediate is reacted with γ-methacryloxypropyltrimethoxysilane to obtain the obtained product; The additive is one or more of a water reducing agent, a defoaming agent, and a swelling agent.
2. The polymer mortar according to claim 1, characterized in that The molar ratio of the 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to 1,3,5,7-tetramethylcyclotetrasiloxane is (4-6):
1.
3. The polymer mortar according to claim 2, characterized in that: The molar ratio of the γ-methacryloxypropyltrimethoxysilane to the hydrogen-containing polysiloxane intermediate is (0.9-1.1):
1.
4. The polymer mortar according to claim 1, characterized in that The cement is one or more of fly ash cement 425, fly ash cement 525, slag silicate cement 425, slag silicate cement 525, general silicate 425 cement, and general silicate 525 cement.
5. The polymer mortar according to claim 1, characterized in that: The redispersible latex powder is one or more of ethylene / vinyl acetate copolymer, vinyl acetate / versatate copolymer, and acrylic acid copolymer.
6. The method for preparing the polymer mortar with the function of durable carbon dioxide absorption according to any one of claims 1 to 5, characterized in that: Mix cement, 10-20 mesh quartz sand, 20-40 mesh quartz sand, 40-70 mesh quartz sand, 70-100 mesh quartz sand, silica fume, redispersible latex powder, admixture and organic amine according to mass parts, stir evenly to obtain dry mortar, add 10% to 15% water of the mass of the dry mortar and mix evenly to obtain polymer mortar.
7. The method for preparing polymer mortar according to claim 6, characterized in that: The organic amine is prepared by the following method: S1: Add end-capping agents 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 1,3,5,7-tetramethylcyclotetrasiloxane into a reactor, introduce protective gas, raise the temperature to 70-90° C., add an alkaline catalyst, and react for 7-10 hours to obtain an amino-terminated hydrogen-containing polysiloxane intermediate; S2: Under a protective gas atmosphere, toluene and γ-methacryloxypropyltrimethoxysilane are added to a reactor, the temperature is raised to 60-80°C, a Karstedt catalyst is added, and then an amino-terminated hydrogenated polysiloxane intermediate is added, the reaction is carried out for 0.5-3h, and toluene is removed to obtain an organic amine.
8. The method for preparing polymer mortar according to claim 7, characterized in that: The alkaline catalyst is one or more of sodium hydroxide, potassium hydroxide, and tetramethylammonium hydroxide.
Citation Information
Patent Citations
Preparation method of waterproof anti-crack mortar
CN115650678A
Degraded amine solution as performance enhancer
EP4317103A1
Polymer cement grout mortar
JP2015127283A
Eco-friendly polymer mortar improving waterproof and anticorrosive functions
KR101365606B1
Admixture for Improving Carbonation Curing, Manufacturing Method the Admixture and Mortar Product Using the Admixture
KR102627082B1